A reduction of sucrose phosphate synthase (SPS) activity affects sucrose/starch ratio in leaves but does not inhibit normal plant growth in rice. (December 2016) - Hashida, Yoichi; Hirose, Tatsuro; Okamura, Masaki; Hibara, Ken-ichiro; Ohsugi, Ryu; Aoki, Naohiro
Highlights: We analyzed rice mutants with defects in sucrose phosphate synthase (SPS) genes. A 50% reduction in SPS activity did not affect sucrose/starch ratio in rice leaves. An 84% reduction in SPS activity caused increase in starch content in rice leaves. An 84% reduction in SPS activity did not inhibit normal plant growth in rice. Abstract: Sucrose phosphate synthase (SPS) has been shown to mediate sucrose/starch ratio in plant leaves through studies of 'starch leaf' species that mainly accumulate starch in their leaves. However, the contribution of SPS to sucrose/starch ratio in rice leaves, which mainly accumulate sucrose (i.e., 'sugar leaf'), has not been confirmed due to inconsistencies in the results of previous studies. In this study, we analyzed mutant lines with reduced SPS activity, which were generated using Tos17 insertion, RNAi, and the CRISPR/Cas9 system. The knockdown and knockout mutants of OsSPS1 showed a 29–46% reduction in SPS activity in the leaves, but the carbohydrate content in the leaves and plant growth were not significantly different from those of wild-type plants. In a double knockout mutant of OsSPS1 and OsSPS11 ( sps1/sps11 ), an 84% reduction in leaf SPS activity resulted in higher starch accumulation in the leaves than in the wild-type leaves. However, the sps1/sps11 plants grew normally, which is in contrast to the inhibited growth of SPS mutants of Arabidopsis thaliana, a typical starch leaf plant. These results suggest that SPS has a smaller effect on the sucrose/starch ratio in leaves and growth of rice than on starch leaf species.